Serum lipids and prostate cancer. Issue 4 (16th March 2021) - Garrido, Manuel M.; Marta, José C.; Ribeiro, Ruy M.; Pinheiro, Luís C.; Guimarães, João T.
Abstract: Background: Conflicting results are found in the literature relating serum lipids levels and prostate cancer. Some results imply a relationship between them; others contradict this association. The purpose of this study was to investigate a possible association between serum lipids levels and prostate cancer, at time of diagnosis. Methods: We measured serum levels of total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides in 237 patients submitted to a prostate biopsy, with PSA between 2 and 10 ng/ml. Patients without cancer at biopsy were used as controls, and the others were considered as cases. No information about lipid‐lowering therapy, including statins, was available neither in cases nor in controls. Cases were divided into risk groups, according to the disease severity, based on staging. Lipids levels were compared between groups, using parametric and nonparametric tests. Logistic regression analysis and odds ratios were calculated. Results: LDL and total cholesterol levels were lower in patients with cancer, with the difference being statistically significant for LDL cholesterol ( p  = 0.010) and borderline for total cholesterol ( p  = 0.050). No significant differences were found between the several risk groups. Odds ratios for low LDL cholesterol (<130 mg/dl) and low total cholesterol (<200 mg/dl), with prostate cancer as the outcome, were 1.983 and 1.703, respectively. There were no significant differences between cases and controls for the other lipids. Conclusion: Lower LDL cholesterol (<130 mg/dl) and lower total cholesterol (<200 mg/dl) serum levels seem to associate with prostate cancer, at time of diagnosis. Abstract : Serum levels of triglycerides, HDL, LDL and total cholesterol were measured in 237 patients submitted to a prostate biopsy (PSA range: 2‐10 ng/mL). Lower LDL and lower total cholesterol levels seem to associate with prostate cancer, at time of diagnosis.